Impact of Forensic Accounting on University Financial System in Nigeria - Osho Augustine E. (European Scientific Journal, ESJ, 2017)
This study examines the effect of forensic accounting on University financial system in Nigeria. The University cannot run without finance which required proper management on the side of the University management so as to avoid mismanagement of fund. Two theories that are of interest to this study Profession Theory and Relative Size Factor Theory are reviewed alongside with the literature reviewed accordingly. The study used ex-post factor research design using data analysis of financial information extracted from audited Financial Statement for the years 2005 to 2014 which is used to examine how an independent variable, present prior to the study, affects a dependent variable. In order to arrive at the testable conclusion, stratified and purposive random sampling techniques were adopted. Simple and multiple regression analysis were used in this research work with the model findings which revealed that University Financial System in Nigeria is significantly affected by the combine effect of all the exogenous variables. It is recommended that University management and the stakeholders should utilize the findings of the study in taking decisions with respect to efficient management of all the components of Forensic Accounting in order to grow their University.